ANALISIS REGRESI LOGISTIK ORDINAL SPASIAL STATUS KETAHANAN PANGAN PADA KABUPATEN/KOTA DI INDONESIA TAHUN 2020 - DEWI, NI NYOMAN UTAMI; SUSILAWATI, MADE; SRINADI, I GUSTI AYU MADE (E-Jurnal Matematika; Vol 12 No 4 (2023), 2023)
Food is a basic need which is a right for humans to survive and has an important role so that an arrangement is needed that describes the level of food security in each region. Food security status shows the food stability of a region in terms of availability, access, and consumption of food for the local populace. The diversity of regencies/cities gives a variance effect in the results of food security so that the spatial influence is included in modeling the status of food security owing to the likelihood of interactions in our research between regions with one another, meaning that the condition of food security in regencies/cities is influenced by the condition of neighboring regencies/cities. Based on this, a model is that may be utilized to assess the state of food security is required in districts/cities in Indonesia in 2020. Logistic regression analysis is one technique that may be utilized to create the model regression analysis. Logistic regression analysis is a regression method that tests whether there is a probability the independent variable has the ability to predict the dependent variable.